Preliminary assessment of coastal erosion and local community adaptation in Sayung coastal area, central java – Indonesia - Marfai, Muh Aris (Quaestiones Geographicae, 2012)
Dynamic environment in coastal area, especially due to coastal erosion process, has negative impact on human environment. Sayung coastal area, located in Central Java-Indonesia, has experienced severe impact of coastal erosion. As the result of the coastal erosion, hundreds of settlement located in coastal area has been destructed. Moreover, fishponds as the land use dominated in the coastal area also has been severely destroyed. Besides the coastal erosion, increasing of inundated area due to sea level rise also threaten the local community. Although devastating impact suffering the coastal area, the people of Tambaksari, as the part of Sayung area, decided to live and adapt with the coastal erosion. This paper aims to identify the coastal erosion and understand adaptation strategies held by the local community related to reduce the impact of the coastal erosion. Based on this research, various adaptation strategies has been identified, namely (1) Planting mangrove alongside the shoreline, (2) elevating the ground level, (3) building staged house, (4) utilizing deep well for freshwater supply, (5), maintaining social interaction with mainland community, (6) Collecting fish from the mangrove as the food, and (7) changing work into the tourism sector.